Retrospective, Relevance, and Trends of Software Agents, Environments and Applications School (WESAAC) - Gonçalves, Enyo; Cortés, Mariela; Oliveira, Marcos de; Veras, Nécio; Falcão, Mário; Castro, Jaelson (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2016)
Multi-Agent Systems (MAS) software has been increasing dramatically in last years. In this context, the Software Agents, Environments and Applications School (WESAAC) is a Brazilian event of MAS which is in its tenth edition. When studying a research area, it is important to identify the most active groups, topics, the research trends and so forth. This study aims to investigate how the WESAAC is evolving, by analyzing the papers published in its 9 editions. We adopted a research strategy that combines scoping study and systematic review good practices. We identify the most active institutions and authors, the main topics discussed, the types of the contributions, the conferences and journals that have most referenced WESAAC papers, the publications with the greatest impact, and the trends in MAS. We found 116 papers over the 9 WESAAC editions, which were analyzed and discussed.